HIV-1 Infection Does Not Change Disease Course or Inflammatory Pattern of SARS-CoV-2-Infected Patients Presenting at a Large Urban Medical Center in New York City. (28th January 2021) - Laracy, Justin; Zucker, Jason; Castor, Delivette; McMahon, Donald J; Guo, Tai Wei; Yan, Michael; Shalev, Noga; Scherer, Matthew; Gordon, Peter; Sobieszczyk, Magdalena; Yin, Michael T
Abstract: Background: The clinical impact of coronavirus disease 2019 (COVID-19) among people with HIV (PWH) remains unclear. In this retrospective cohort study of COVID-19, we compared clinical outcomes and laboratory parameters among PWH and controls. Methods: Sixty-eight PWH diagnosed with COVID-19 were matched 1:4 to patients without known HIV diagnosis, drawn from a study population of all patients who were diagnosed with COVID-19 at an academic urban hospital. The primary outcome was death/discharge to hospice within 30 days of hospital presentation. Results: PWH were more likely to be admitted from the emergency department than patients without HIV (91% vs 71%; P  = .001). We observed no statistically significant difference between admitted PWH and patients without HIV in terms of 30-day mortality rate (19% vs 13%, respectively) or mechanical ventilation rate (18% vs 20%, respectively). PWH had higher erythrocyte sedimentation rates than controls on admission but did not differ in other inflammatory marker levels or nasopharyngeal/oropharyngeal severe acute respiratory syndrome coronavirus 2 viral load estimated by reverse transcriptase polymerase chain reaction cycle thresholds. Conclusions: HIV infection status was associated with a higher admission rate; however, among hospitalized patients, PWH did not differ from HIV-uninfected controls by rate of mechanical ventilation or death/discharge to hospice.